ANALISIS PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA BANK UMUM SYARIAH - Restrien, Johar; Paramitha, Dyah Ayu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to determine the effect partially and simultaneously of the variable company size, profitability and leverage on Islamic Social Reporting at Islamic Commercial Banks for the period 2015-2018. This study uses ex post facto research methods with a quantitative approach. Analysis using multiple linear regression with SPSS for windows version 24 software. The conclusion in this study is the results of the study show that company size and profitability partially do not have a significant effect on Islamic Social Reporting. Leverage partially shows a significant effect on Islamic Social Reporting. While the simultaneous testing of Company Size, Profitability, Leverage shows that simultaneously there is no significant effect on Islamic Social Reporting.